2017
DOI: 10.15540/nr.4.3-4.125
|View full text |Cite
|
Sign up to set email alerts
|

Small-World Network Analysis of Cortical Connectivity in Chronic Fatigue Syndrome Using Quantitative EEG

Abstract: The aim of this study was to explore the relationship between complex brain networks in people with Chronic Fatigue Syndrome (CFS) and neurocognitive impairment. Quantitative EEG (qEEG) recordings were taken from 14 people with CFS and 15 healthy controls (HCs) during an eye-closed resting condition. Exact low resolution electromagnetic tomography (eLORETA) was used to estimate cortical sources and perform a functional connectivity analysis. The graph theory approach was used to characterize network representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…Females made up the largest proportion of participants. There were only 10 studies which reported race, where majority of the participants were Caucasian [12,19,21,26,27,37,41,47,48,52]. Mean age across all studies was 40.9 years for ME/CFS patients and 39.07 years for HCs.…”
Section: Participant and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Females made up the largest proportion of participants. There were only 10 studies which reported race, where majority of the participants were Caucasian [12,19,21,26,27,37,41,47,48,52]. Mean age across all studies was 40.9 years for ME/CFS patients and 39.07 years for HCs.…”
Section: Participant and Study Characteristicsmentioning
confidence: 99%
“…In all twin studies, levels of zygosity were assessed and ascertained at 99.9% [12,21,27]. 47 of the 55 identified papers included participants that fulfilled the requirements of being diagnosed with the Fukuda criteria [12,14,[16][17][18][19][21][22][23][24][25][26][27][28]30,31,[34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Three of the papers used the more stringent CCC criteria to classify ME/CFS patients [15,29,42].…”
Section: Participant and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DSQ-1 has been used for a variety of purposes, including documenting specific ME and CFS vision-related abnormalities ( 27 ). In addition, using QEEG recordings, Zinn et al ( 28 ) estimated cortical sources and perform a functional connectivity analysis on 84 Brodmann areas representing the entire cortex. Neurocognitive impairment, as measured by the DSQ-1's cognitive composite score, was negatively associated with small-worldness index for the delta band under observation.…”
Section: Dsq-1mentioning
confidence: 99%